Street Crime during Covid-19 Pandemic in Perspective of Routine Activity Law Theory and it Influence on Indonesian Criminal Law - Ida Hasan; Holy One Singadimedja; Yogi Yasa Wedha; Sara Ida Magdalena Awi; Edy Nurcahyo (International Journal of Science, Technology & Management, 2020)
The initial prediction is that the condition of covid-19 pandemic will shake people's lives in all aspects, and this condition has a great potential for rising crime. With all of its character, it is very interesting to discuss how street crime developed during the Covid-19 pandemic. This study use a mixed research method, where data is collected from facts in the field, legal sources or applied regulations, associated with legal materials obtained from literature review research and overall data obtained from both primary data and secondary data. The conclusion from this research is that street crime during the Covid-19 Pandemic cannot be stated expressly decreased or increased for each region has dynamics that differ from one another according to the characteristics of the region. The correlation of PSBB policy during the Covid-19 Pandemic with the level of street crime in the perspective of routine activity theory can be seen from several street crimes that change the type and location of their objects / targets as well as the increasing number of drug and cybercrime cases that are striking. PSBB conditions during Pandemic Covid-19 against crimes that require a new system that is integrated with the internet, a pattern of punishment with massive amounts of assimilation to reduce the density of prison and a virtual court examination system that should be a part of the criminal justice system in Indonesia